2004
DOI: 10.1021/cm034999b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ru(II) Tris(1,10-phenanthroline)-Electron Acceptor Dyads Incorporating the 4-Benzoyl-N-methylpyridinium Cation or N-Benzyl-N‘-methyl Viologen. Improving the Dynamic Range, Sensitivity, and Response Time of Sol−Gel-Based Optical Oxygen Sensors

Abstract: The title compounds were synthesized by Sonogashira coupling reactions of appropriate Ru(II) complexes with the electron acceptors. Characterization was conducted in solution and in frozen matrixes. Finally, the title compounds were evaluated as dopants of sol-gel materials. It was found that the intramolecular quenching efficiency of 4-benzoyl-Nmethylpyridinium cation in solution depends on the solvent: photoluminescence is quenched completely in CH 3 CN, but not in methanol or ethanol. On the other hand, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Synthesis of the metal complexes : [Pt(tpy)(CC‐CCCH 2 OH)][OTf] ( 1 ) was synthesized as reported previously 20. The compounds Me 3 SiCCC 6 H 4 CH 2 Br,21 Me 3 SiCC‐CCCH 2 Br,22 [Pt(tpy)Cl][OTf],23 and [Pt(tpy)(CH 3 CN)][OTf] 2 14, 24 were synthesized according to literature methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of the metal complexes : [Pt(tpy)(CC‐CCCH 2 OH)][OTf] ( 1 ) was synthesized as reported previously 20. The compounds Me 3 SiCCC 6 H 4 CH 2 Br,21 Me 3 SiCC‐CCCH 2 Br,22 [Pt(tpy)Cl][OTf],23 and [Pt(tpy)(CH 3 CN)][OTf] 2 14, 24 were synthesized according to literature methods.…”
Section: Methodsmentioning
confidence: 99%
“…(1) was synthesized as reported previously. [20] The compounds Me 3 Si-CCC 6 H 4 CH 2 Br, [21] Me 3 SiCC-CCCH 2 Br, [22] [23] and [14,24] were synthesized according to literature methods.…”
Section: Synthesis Of the Metal Complexesmentioning
confidence: 99%
“…Oxygen sensing has been accomplished through quenching of the fluorescence of N -(3-trimethoxysilylpropyl)-2,7-diazapyrenium bromide incorporated into a highly porous aerogel through direct co-condensation and post-synthesis grafting [91, 92]. It was found that co-condensation provided a more uniform distribution of the dye and more effective interrogation of the resulting photoluminescence.…”
Section: Small Molecules and Ionsmentioning
confidence: 99%
“…It was found that co-condensation provided a more uniform distribution of the dye and more effective interrogation of the resulting photoluminescence. The incorporation of ruthenium complexes into a variety of materials has been applied to detection and quantification of oxygen [82, 92-95]. In the case of the ruthenium complexes, covalent modification techniques were found to yield notably more linear Stern-Volmer plots (I 0 /I vs. oxygen concentration) than techniques that employed entrapment of the dyes [93].…”
Section: Small Molecules and Ionsmentioning
confidence: 99%
“…Many studies have been conducted on strategies for synthesizing a highly efficient dye. For example, rod- [ 1 , 2 ] and star-shaped [ 3 , 4 , 5 , 6 ] hydrocarbons that expand π-conjugation to two dimensions can be used to control the emission color of a dye with high efficiency.…”
Section: Introductionmentioning
confidence: 99%